Factors that influence adoption intention towards QR code payment at merchants in Indonesia - Meilinda Arwanto; Erna Andajani; Siti Rahayu (Southeast Asian Journal of Service Management, 2025)
This study aims to determine the influence of independent variables, including Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Government Support, and Quality of Internet Connection, on the dependent variable Adoption Intention. The object of this research is the QRIS (Quick Response Code Indonesia Standard) payment system, a type of payment using QR codes applicable in Indonesia, created by Bank Indonesia. This study uses primary data from questionnaires distributed using non-probability sampling techniques to owners or decision-makers of merchants whose operating for at least one year and have been using QRIS for a minimum of six months in Indonesia. Conducted with a quantitative approach, this research employs the Partial Least Square - Structural Equation Modeling (PLS-SEM) testing method. Based on 162 respondents, the results indicate that Performance Expectancy, Facilitating Conditions, and Quality of Internet Connection have a positive and significant influence on Adoption Intention. Meanwhile, Effort Expectancy, Social Influence, and Government Support show a positive but not statistically significant influence on Adoption Intention.